Silent coup of the guardians : the influence of U.S. military elites on national security - Schmidt, Todd Andrew (Studies in civil-military relations., 2023)
"Understanding US national security and foreign policy decision-making requires understanding the actors: the president, civilian elites, advisors, bureaucracies, and institutions. In Silent Coup of the Guardians, Todd Schmidt demonstrates that military elites constitute an epistemic community and, as such, play a unique role due to their exceptional influence over both policy process and outcome. His findings help explain nuanced relationships between military elites, the president, and Congress; decision-making in national security and foreign policy; and civil-military balance of power relations that suggest a potential trend of praetorian behavior among U.S. military elites. He concludes that a silent coup of the guardians has occurred, and that professionals and citizens need to ask what should be done to re-balance civil-military relations"--